EDUCATIONAL MASTER-CLASS ON ARTERIAL HYPERTENSION AND CARDIOVASCULAR RISK. MOSCOW, SEPTEMBER 12-13, 2007 (Рациональная фармакотерапия в кардиологии)
Educational master-class on arterial hypertension and cardiovascular risk. Moscow, September 12-13, 2007.